Relationship between psychological need satisfaction and work engement among workers in tcm centre - Nur Syahira Zainal Abidin; Nursyazwani Irdina Rozaiman; Nurul Atiqah Rosli; Siti Humaira Baharuddin (2023)
The growing recognition of the connection between employees' wellbeing, working conditions, satisfaction and productivity has increased the requirement for understanding the need for a culture of health, wellbeing and certainty in the workplace. This study aimed to investigate the relationship between the autonomy, competency and relatedness with work engagement among workers in TCM Centre. Data were gathered from 384 TCM Centre workers in Kelantan using the validated questionnaire. The results for Pearson’s Correlation Coefficient shown that there was a significant relationship between autonomy, competency and relatedness with the P-value less than 0.001 respectively. Therefore, the employer must always ensure that the autonomy and relatedness of the workers at the Traditional and Complementary Medicine Center is always good and in a good state because they are backbone of progress, sustainability and success in Traditional and Complementary Medicine organizations. Keywords: Influencing Factors, Need for Psychological Satisfaction, Autonomy, Competence, Relatedness